Cangkang Telur dan Air Leri Sebagai Nutrisi Hidroponik DFT (Deep Flow Technique) Bagi Pertumbuhan Bayam Merah dan Bayam Hijau - Yuda Arif Yuniansyah; Ahmad Arif Darmawan; Slamet Rohadi Suparto; Agus Suyanto (Savana Cendana, 2022)
The purpose of this research is to know the effect of adding the egg shell and washing rice water to the solution of nutrients (AB-mix ) on the growth and results of red and green spinach, to know the growth of red spinach and green spinach and to know the interaction between egg shell and rice washing water addition in to AB Mix solution on the growth and results of red and green spinach. The method used in this research was Complete Randomized Block Design (RAKL) with two factors with 3 replications. Factor first was A0 treatment (AB Mix 1%), A1 (AB Mix 1% and egg shell 1%), A2 (AB Mix 1% and rice washing water 1%), A3 (AB Mix 1%, egg shell 0.5% and rice washing water 0.5%) and factor the second was are red spinach and green spinach varieties. The parameters measured were plant height, leaf number, leaf area, root length, fresh crown weight, dry crown weight, fresh root weight, dry root weight. The results showed that A2 (AB Mix 1% and rice washing water 1%) could increase plant height, leaf number, leaf area, root length,fresh crown weight, fresh root weight, dry crown weight and dry root weight in red spinach and green spinach. Green spinach growth was better than the red spinach. The interaction between egg shell and rice washing water addition in to AB Mix solution with the type of spinach took effect in the number of leaves, plant height and dry root weight.